2005
DOI: 10.1103/physrevb.72.024112
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure experimental and theoretical investigations on the fluorite structured compoundAuAl2

Abstract: Diamond anvil cell ͑DAC͒ based resistance measurements are carried out in AuAl 2 to the pressures of about 25 GPa for the first time. The data indicate possibility of phase transition around 12 GPa. High pressure data obtained using Elettra synchrotron source confirm the transformation of AuAl 2 from ambient CaF 2 to orthorhombic phase. The high precision P-V data when transformed to universal equation of state does not show any deviation from linearity. The first principles electronic band structure calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 30 publications
6
21
0
Order By: Relevance
“…1. It is found that the calculated equation of state of AuAl 2 in the cubic fluorite structure is in agreement with the available experimental of Garg et al [25] and theoretical data of Verma et al [26]. Our calculated lattice constant and bulk modulus agree well with the latest theoretical data [26].…”
Section: Structural Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…1. It is found that the calculated equation of state of AuAl 2 in the cubic fluorite structure is in agreement with the available experimental of Garg et al [25] and theoretical data of Verma et al [26]. Our calculated lattice constant and bulk modulus agree well with the latest theoretical data [26].…”
Section: Structural Propertiessupporting
confidence: 93%
“…Tütüncü et al investigated the electronic and dynamical properties of AuAl 2 using first-principles [24]. Garg et al also investigated the effect of pressure on the structure and electronic of AuAl 2 performing experimental and theoretical investigations [25]. Verma et al confirmed the high-pressure orthorhombic phase of AuAl 2 using projector augmented wave (PAW) pseudopotentials method [26].…”
Section: Introductionmentioning
confidence: 96%
“…1 A small group of intermetallics with substantial covalent bonding are also known. 7 Evidence of disorder at high pressure was also observed as the broadening of x-ray diffraction lines. While the fluorite is the stable form at room temperature for all the Au compounds and PtAl 2 , it occurs as the high temperature modification for PtGa 2 and PtIn 2 .…”
Section: Introductionmentioning
confidence: 92%
“…Electrical resistance measurements up to a maximum pressure of 10 GPa were made using an opposed Bridgman anvil set-up with 12-mm diameter tungsten carbide anvils [41] that is mounted in a hydraulic press. A pair of pyrophyllite gaskets, with a thickness 200 µm each, and with a central hole of 3 mm in diameter, was employed as the pressure chamber.…”
Section: Electrical Resistancementioning
confidence: 99%